I-F Starting Method for Smooth and Fast Transition to Sensorless Field Oriented Control of Bldc Motors - Baratieri, Cassio Luciano; Pinheiro, Humberto (Eletrônica de Potência, 2014)
This paper proposes an I-f starting method for smooth and fast transition from open- loop frequency control to sensorless field oriented control (FOC) of BLDC motors. The method is divided in three stages: (i) initially the rotor is aligned with a desired angular position; (ii) then, the stator currents are controlled in an arbitrary reference frame to impose the angular frequency of the rotating magnetic field with a suitable profile; (iii) finally, a smooth transition between the arbitrary and the rotor reference frames is accomplished by recalculating the current controller states and references. The proposed method preserves the electromagnetic torque magnitude during the transition avoiding undesired transients. In addition, a procedure based on mechanical model is described to determine a suitable ramp profile. Moreover, the estimated rotor position that is required for FOC as well as for the proposed method is computed by using the estimated back-EMFs from a Luenberger observer. The good performance and robustness under no-load and full load conditions of the proposed starting method are demonstrated by simulation and experimental results.